An atheism that is not humanist emerges in French thought - Geroulanos, Stefanos, 1979- (Cultural memory in the present., 2010)
This book seeks to explain the critiques of humanism and the "negative" philosophical anthropologies that dominated mid-century philosophy and traces the appearance of a new, non-humanist atheism in twentieth-century French thought.